1990
DOI: 10.1128/jvi.64.1.173-184.1990
|View full text |Cite
|
Sign up to set email alerts
|

Activity of simian DNA-binding factors is altered in the presence of simian virus 40 (SV40) early proteins: characterization of factors binding to elements involved in activation of the SV40 late promoter

Abstract: The early proteins of simian virus 40 (SV40) large T and small t antigen (T/t antigen) can each cause the transcriptional activation of a variety of cellular and viral promoters. We showed previously that simian cellular DNA-binding factors (the Band A factors) bind to sequences within the SV40 late promoter which are important for transcriptional activation in the presence of the SV40 early proteins. Band A factors isolated from simian cells which produce T/t antigen (COS cells or SV40-infected CV-1 cells) ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
1

Year Published

1991
1991
1993
1993

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 50 publications
1
18
0
1
Order By: Relevance
“…T antigen also binds transcription factor TEF-1 (27). Since TEF-1-binding sites are important for SV40 late transcription (12,15,24,26,34,42), T antigen-TEF-l interactions could play a role in making the SV40 late promoter a particularly good substrate for T antigen activation. The SV40 late promoter lacks a TATA box, but among sequences surrounding the major late transcription initiation site at nt 325 and important for late transcription are some which resemble Inr elements.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…T antigen also binds transcription factor TEF-1 (27). Since TEF-1-binding sites are important for SV40 late transcription (12,15,24,26,34,42), T antigen-TEF-l interactions could play a role in making the SV40 late promoter a particularly good substrate for T antigen activation. The SV40 late promoter lacks a TATA box, but among sequences surrounding the major late transcription initiation site at nt 325 and important for late transcription are some which resemble Inr elements.…”
Section: Discussionmentioning
confidence: 99%
“…The SV40 late promoter lacks a TATA box, but among sequences surrounding the major late transcription initiation site at nt 325 and important for late transcription are some which resemble Inr elements. The TBP is known to be important for in vitro transcription of promoters which lack obvious TATA boxes (12,15,24,26,34,42) and may also bind directly to Inr elements (65).…”
Section: Discussionmentioning
confidence: 99%
“…Several mutants which transactivated the RSV LTR less well than did wild-type T transactivated the SV40 late promoter at wild-type levels. This probably reflects the fact that these two transcriptional control regions are quite different (21,25,29). Different transcription factors are involved in transcription from these two promoters, and therefore the role played by T antigen in transactivation of each may be different.…”
Section: In303 In346mentioning
confidence: 99%
“…Many studies have focused on defining sequence elements within the SV40 late promoter that are involved in mediating transactivation by T antigen (10,38). Other studies have demonstrated that the presence of T antigen causes alterations in the pattern of cellular transcription factors able to recognize these key sequences, but the mechanism by which these changes are caused is not known (4,20,21).…”
mentioning
confidence: 99%
“…Both the 72-bp and 21-bp elements can promote transcription in an orientation-independent manner, and factors that bind to them are potential targets for TAg. Recently, sequences within the enhancer have been shown to play a role in TAg activation (5,8,14), and it is hoped that cell-free transcription systems will permit biochemical characterization of the molecules involved.…”
Section: Earlymentioning
confidence: 99%